The potential application of nanomaterials for ferroptosis-based cancer therapy. (11th June 2021) - Li, Yingze; Wei, Xueyan; Tao, Feng; Deng, Cuijun; Lv, Cheng; Chen, Chang; Cheng, Yu
Abstract: Ferroptosis is a new type of programmed cell death, which is expected to become an important strategy of cancer treatment. Traditional strategies for inducing iron death are small molecule inducers based on biological agents. However, because of their poor water solubility, low cell targeting ability and fast metabolism in vivo, it is difficult for molecular drugs to play the long-acting role of ferroptosis induction. With the further study of ferroptosis and development of nanotechnology, nanomaterials have been proved to be more efficient drugs for inducing ferroptosis than those biological drugs. Therein, iron-based nanomaterials can directly release high concentrations of irons and increase reactive oxygen species levels in cells, which produce a better induction effect for ferroptosis. Whereas, it is challenging to differentiate nanoparticle-induced ferroptosis and traditional inducing strategies, elucidate the detailed mechanisms and further classify the synthetical methods of nanomaterials. For better guidance on the development of anticancer strategies, comprehensive summary of the latest developments of ferroptosis related nanomaterials, especially iron-based nanomaterials are in urgent need. In the paper, we summarized the main mechanisms of ferroptosis, highlighted the latest developments of nanomaterials for ferroptosis, and emphasized the advantages of iron-based nanomaterials for ferroptosis. The future prospect in this field was also discussed, paving the way for the related nanomaterials in the clinical cancer therapy.